Additions to the knowledge of Manota Williston (Diptera: Mycetophilidae) from the Neotropical region, with description of four new species - Kurina, Olavi; Hippa, Heikki (Zootaxa, 2021)
The Neotropical species of the genus Manota Williston are studied, based on material of 146 specimens from French Guiana, Ecuador, Nicaragua, Dominica and the Dominican Republic. Four new species are described, viz. M. corniculata sp. n. (French Guiana), M. pseudocavata sp. n. (French Guiana), M. truuverki sp. n. (French Guiana) and M. vladi sp. n. (Dominican Republic). Manota defecta Williston, 1896, the type species of the genus, is listed from Dominica, representing the first record since its description more than a century ago from a Southern Caribbean Island, St. Vincent. New records of 13 additional species are provided: M. acutistylus Jaschhof & Hippa, 2005 (Dominica), M. aligera Hippa, Kurina & Sääksjärvi, 2017 (French Guiana), M. digitata Hippa, Kurina & Sääksjärvi, 2017 (French Guiana), M. iota Hippa & Kurina, 2013 (French Guiana), M. micula Hippa & Kurina, 2013 (French Guiana), M. nordestina Kurina, Hippa & Amorim, 2018 (French Guiana), M. parva Jaschhof & Hippa, 2005 (Nicaragua), M. pauloides Hippa, Kurina & Sääksjärvi, 2017 (Ecuador), M. perplexa Kurina, Hippa & Amorim, 2017 (Nicaragua), M. rotundistylus Jaschhof & Hippa, 2005 (Ecuador), M. serrulata Hippa, Kurina & Sääksjärvi, 2017 (French Guiana), M. spinosa Jaschhof & Hippa, 2005 (French Guiana), M. subaristata Kurina, Hippa & Amorim, 2017 (Ecuador). The number of Neotropical Manota species has risen to 96.